PENINGKATAN MUTU SEKOLAH MELALUI PENDEKATAN PROSES TOTAL QUALITY MANAGEMENT (TQM) DI SMPIT NURUL HIKMAH PENAJAM PASER UTARA - Arbiyah Herlinawati; Novi Justica Rofiyati; Azainil; Nurul Chasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quality education does not only focus on academic achievement, but also on the formation of character, skills, and critical thinking of students. Therefore, an effective management system is needed to improve the quality of education. This study aims to describe the implementation of Total Quality Management (TQM) and the process approach, the steps of its implementation, the benefits of the process approach, and the implementation of the process approach at SMPIT Nurul Hikmah Penajam Paser Utara. The method used is descriptive qualitative with a literature approach. The references used in writing are journals, books and previous research papers related to the topics discussed. The process approach in improving school quality at SMPIT Nurul Hikmah has proven effective in improving the quality of education. With systematic planning, directed implementation, continuous evaluation, and the involvement of all stakeholders, schools are able to create a better learning environment.